Government Deficit Shocks and Okun's Coefficient Volatility: New Insights on the Austerity versus Growth Debate - Binh Thai Pham; Hector Sala (Institute of Labor Economics (IZA), 2019)
This paper connects two salient economic features: (i) Fiscal shocks have asymmetric effects across business cycle phases (Gechert et al., 2019); (ii) Okun's coefficient is time varying and may be unstable. The intertwined dynamic behavior of fiscal shocks and unemployment-output trade-offs are studied in this paper using state-of-the-art TVP-VAR modelling techniques applied to the analysis of six selected economies: France, Japan, Spain, Sweden, the United Kingdom (UK), and the Unites States of America (USA). We confirm the heterogeneity of Okun's coefficient across country, and its time-varying nature across time, showing in addition its fluctuation around a reference long-run value. We document a significant short-run impact of fiscal shocks on Okun's trade-off which, based on the experience of the Global Financial Crisis, becomes larger in periods of economic turmoil. Okun's coefficient is most volatile in Spain and most stable in Sweden and Japan, with France, UK and USA in between. Policy wise, we claim that austerity policies may have unexpected adverse effects on job creation if implemented during slumps, precisely when the labor market sensitivity with respect to the performance of the product market is likely to be more acute.
Keywords: E24; E32; E62; 330; fiscal shocks; Okun's coefficient; business cycle; austerity; TVP-VAR